Analysis of the Implementation of Environmental Risk Factor Monitoring in Tuberculosis Management - Rifai, Achmad (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Tuberculosis (TB) remains a major health issue in Indonesia, closely linked to environmental risk factors such as poor ventilation and inadequate sanitation. Objective: This study aimed to analyze the implementation of environmental risk factor monitoring in TB control efforts at Hutabaginda Health Center, North Tapanuli District. Research Methods: a qualitative approach with a case study design was used. Data were collected through in-depth interviews, participatory observations, and document reviews, and analyzed thematically with data triangulation. Results: The study found that although policies for controlling environmental risks exist, implementation faces challenges including limited trained personnel, inadequate sanitation facilities, weak supervision, and suboptimal coordination with local governments. Conclusion: the health service management system at Hutabaginda Health Center has not yet been optimal in controlling environmental risk factors for TB. It is recommended that the health center strengthen healthcare worker training, improve sanitation facilities, enhance internal supervision, and intensify cross-sectoral coordination to improve TB control effectiveness.